2011
DOI: 10.1007/s00520-011-1236-3
|View full text |Cite
|
Sign up to set email alerts
|

Ginger (Zingiber officinale) reduces acute chemotherapy-induced nausea: a URCC CCOP study of 576 patients

Abstract: Purpose Despite the widespread use of antiemetics, nausea continues to be reported by over 70% of patients receiving chemotherapy. Methods In this double blind, multicenter trial, we randomly assigned 744 cancer patients to four arms: 1) placebo, 2) 0.5g ginger, 3) 1.0g ginger, or 4) 1.5g ginger. Nausea occurrence and severity were assessed at a baseline cycle and the two following cycles during which patients were taking their assigned study medication. All patients received a 5-HT3 receptor antagonist anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
239
1
23

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(265 citation statements)
references
References 31 publications
2
239
1
23
Order By: Relevance
“…Indeed, clinical trials have reported a significant improvement in CINV where ginger was combined with standard treatment with a setron class drug. [22,30] Recently, the crystal structure of the murine 5-HT3 receptor in the apo (or unbound) form was solved using X-ray crystallography at 3.5Å resolution (Figure 2). [5] Prior to this, structural studies had relied on homology models using templates from other CYS loop receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, clinical trials have reported a significant improvement in CINV where ginger was combined with standard treatment with a setron class drug. [22,30] Recently, the crystal structure of the murine 5-HT3 receptor in the apo (or unbound) form was solved using X-ray crystallography at 3.5Å resolution (Figure 2). [5] Prior to this, structural studies had relied on homology models using templates from other CYS loop receptors.…”
Section: Introductionmentioning
confidence: 99%
“…(25) . Referentes aos 19 estudos restantes foram abordadas as seguintes propriedades terapêuticas com pesquisas envolvendo o gengibre: tratamento da náusea induzida por quimioterapia (26) , função para absorção de Ferro, Zinco e Cálcio (27) , analgésico (28) , antidependência contra o uso crônico da morfina (29) , anti-inflamatório (30) , antimicrobiano (31) , combate à ação da artrite reumatoide (32) , aumento da proteólise muscular em patos (33) , tratamento do câncer de mama (14) , citoprotetor (15) , combate ao vírus sincicial respiratório humano (VSR) (34) , combate a sintomas da Doença de Alzheimer (35) , tratamento da fibrose hepática (36) , proteção contra a genotoxicidade (37) , inibição da enzima Angiotensina I (38) , inibição da motilidade do cólon (39) , atenuação da isquemia cerebral (40) , redução da nefrotoxicidade (41) e neuroprotetor (42) , as quais tiveram um estudo cada publicadas durante o período de análise.…”
Section: Resultsunclassified
“…Bu alanda yapılan çalışmaların daha çok zencefil üzerinde yoğunlaştığı ve bulantı kusma yönetiminde zencefil kullanıldığı görülmektedir. [23][24][25][26][27][28][29][30] Dünyanın pek çok bölgesinde yaygın kullanımı olan zencefil, genellikle baharat ya da gıda desteği olarak geleneksel tıpta yüzlerce yıldır kullanılmaktadır. Roma, Çin, Yunan ve Osmanlı tıp tarihi kayıtları zencefilin tıbbi bir bitki olarak kullanıldığını göstermektedir.…”
Section: Bitkisel Tedavilerunclassified